COVID-19 in the New York City Jail System: Epidemiology and Health Care Response, March–April 2020. (May 2021) - Chan, Justin; Burke, Kelsey; Bedard, Rachael; Grigg, James; Winters, John; Vessell, Colleen; Rosner, Zachary; Cheng, Jeffrey; Katyal, Monica; Yang, Patricia; MacDonald, Ross
Objectives: People detained in correctional facilities are at high risk for infection with severe acute respiratory syndrome coronavirus 2, the virus that causes coronavirus disease 2019 (COVID-19). We described the epidemiology of the COVID-19 outbreak in a large urban jail system, including signs and symptoms at time of testing and risk factors for hospitalization. Methods: This retrospective observational cohort study included all patients aged ≥18 years who were tested for COVID-19 during March 11–April 28, 2020, while in custody in the New York City jail system (N = 978). We described demographic characteristics and signs and symptoms at the time of testing and performed Cox regression analysis to identify factors associated with hospitalization among those with a positive test result. Results: Of 978 people tested for COVID-19, 568 received a positive test result. Among symptomatic patients, the most common symptoms among those who received a positive test result were cough (n = 293 of 510, 57%) and objective fever (n = 288 of 510, 56%). Of 257 asymptomatic patients who were tested, 58 (23%) received a positive test result. Forty-five (8%) people who received a positive test result were hospitalized for COVID-19. Older age (aged ≥55 vs 18-34) (adjusted hazard ratio [aHR] = 13.41; 95% CI, 3.80-47.33) and diabetes mellitus (aHR = 1.99; 95% CI, 1.00-3.95) were significantly associated with hospitalization. Conclusions: A substantial proportion of people tested in New York City jails received a positive test result for COVID-19, including a large proportion of people tested while asymptomatic. During periods of ongoing transmission, asymptomatic screening should complement symptom-driven COVID-19 testing in correctional facilities. Older patients and people with diabetes mellitus should be closely monitored after COVID-19 diagnosis because of their increased risk for hospitalization.